The clinical characteristics and therapeutic outcomes of adult patients with community-acquired spontaneous bacterial meningitis with a fulminant clinical course in Taiwan - Chia-Yi Lien; Chun-Chih Chien; Cheng-Hsien Lu; Wen-Neng Chang (BMC Infectious Diseases, 2023)
Abstract Purpose To examine the clinical characteristics of adult patients with community-acquired spontaneous bacterial meningitis (CASBM) with a fulminant clinical course. Materials and methods The clinical features and therapeutic outcomes of 127 adult CASBM patients were analyzed. The patients were divided into two groups as those with and without a fulminant clinical course. Fulminant clinical course was defined as meningitis presenting initially with marked consciousness disturbance (Glasgow Coma Scale score < 8) or a rapid deterioration in consciousness level within 48 h of hospitalization. Results Among the 127 enrolled patients, 69 had a fulminant clinical course (47 men and 22 women) and 58 did not. The patients with a fulminant clinical course had a significantly higher incidence of end-stage renal disease (ESRD), severe clinical manifestations and higher mortality rate, and the survivors had significantly worse therapeutic outcomes. Klebsiella (K.) pneumoniae (50 strains) was the most important pathogen for the development of a fulminant clinical course, and all strains were susceptible to ceftriaxone and ceftazidime. With treatment, 50.7% (35/69) of the patients with a fulminant clinical course died, and the presence of K. pneumoniae infection was significant prognostic factor. Conclusions The presence of ESRD, initial presentation of altered consciousness, septic shock, seizures and CSF total protein level and K. pneumoniae infection were significantly associated with a fulminant clinical course of adult CASBM, and patients with this specific infectious syndrome had high mortality and morbidity rates. The presence of K. pneumoniae infection is a significant prognostic factor.